Caracterização do perfil dos trabalhadores atuantes no setor da construção civil na cidade de Alegrete-RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Despite the importance of civil construction for the national economy and of being the second most used sector in Brazil, its workforce is still characterized by its low qualification and high turnover. When we consider that the productivity of the workforce is proportional to the level of qualification of the same, the poor formation of the professionals is highly detrimental for the search for better results in the sector, being the knowledge of the needs of these workers and their motivation and dedication during the development of any action aimed at improvements in the sector, essential for the success of these. Therefore, this study aimed to identify the demands for qualification of construction workers in the city of Alegrete / RS, through the application of a questionnaire with questions aimed at the knowledge of their personal, professional profile, level of satisfaction with the sector and even their training and interest in qualification. In order to better understand the local civil construction sector and to describe the managers' perceptions regarding the qualification needs of construction workers in Alegrete, they were also interviewed through the application of questionnaires, engineers and architects who work in the municipality as professionals and representatives of local builders. The results obtained allowed to identify that the area most affected by the lack of skilled workers is in relation to specialized professionals related to the work, that the main problems for the construction sector in the municipality refer to high tax burden and the lack of working capital . In relation to the workers in the construction of the city, it was observed that these present characteristics similar to those in other cities in relation to the low level of education and professional training carried out at the construction site. However, the professionals of Alegrete stand out from being in the age group of 36 to 45 years, workers over 65 years of age, female presence in the construction sites, for working in the construction industry because this is really the sector that would like to to act and mainly for the stability in the function exercised and in the company in which they acted at the moment of the accomplishment of this study.
Keywords: Engenharia civil; Construção civil; Canteiro de obras; Qualificação profissional; Civil Engineering; Civil construction; Construction site; Professional qualification; CNPQ::ENGENHARIAS